The Efficacy of "Foundations," a Digital Mental Health App to Improve Mental Well-being During COVID-19: Proof-of-Principle Randomized Controlled Trial - Silvina Catuara-Solarz; Bartlomiej Skorulski; Iñaki Estella-Aguerri; Claudia Bibiana Avella-Garcia; Sarah Shepherd; Emily Stott; Nicola R Hemmings; Aleix Ruiz de Villa; Laura Schulze; Sophie Dix (JMIR Publications, 2022)
BackgroundAgainst a long-term trend of increasing demand, the COVID-19 pandemic has led to a global rise in common mental disorders. Now more than ever, there is an urgent need for scalable, evidence-based interventions to support mental well-being. ObjectiveThe aim of this proof-of-principle study was to evaluate the efficacy of a mobile-based app in adults with self-reported symptoms of anxiety and stress in a randomized control trial that took place during the first wave of the COVID-19 pandemic in the United Kingdom. MethodsAdults with mild to severe anxiety and moderate to high levels of perceived stress were randomized to either the intervention or control arm. Participants in the intervention arm were given access to the Foundations app for the duration of the 4-week study. All participants were required to self-report a range of validated measures of mental well-being (10-item Connor-Davidson Resilience scale [CD-RISC-10], 7-item Generalized Anxiety Disorder scale [GAD-7], Office of National Statistics Four Subjective Well-being Questions [ONS-4], World Health Organization-5 Well-Being Index [WHO-5]) and sleep (Minimal Insomnia Scale [MISS]) at baseline and at weeks 2 and 4. The self-reported measures of perceived stress (10-item Perceived Stress Score [PSS-10]) were obtained weekly. ResultsA total of 136 participants completed the study and were included in the final analysis. The intervention group (n=62) showed significant improvements compared to the control group (n=74) on measures of anxiety, with a mean GAD-7 score change from baseline of -1.35 (SD 4.43) and -0.23 (SD 3.24), respectively (t134=1.71, P=.04); resilience, with a mean change in CD-RISC score of 1.79 (SD 4.08) and -0.31 (SD 3.16), respectively (t134=-3.37, P<.001); sleep, with a mean MISS score change of -1.16 (SD 2.67) and -0.26 (SD 2.29), respectively (t134=2.13, P=.01); and mental well-being, with a mean WHO-5 score change of 1.53 (SD 5.30) and -0.23 (SD 4.20), respectively (t134=-2.16, P=.02), within 2 weeks of using Foundations, with further improvements emerging at week 4. Perceived stress was also reduced within the intervention group, although the difference did not reach statistical significance relative to the control group, with a PSS score change from baseline to week 2 of -2.94 (SD 6.84) and -2.05 (SD 5.34), respectively (t134= 0.84, P=.20). ConclusionsThis study provides a proof of principle that the digital mental health app Foundations can improve measures of mental well-being, anxiety, resilience, and sleep within 2 weeks of use, with greater effects after 4 weeks. Foundations therefore offers potential as a scalable, cost-effective, and accessible solution to enhance mental well-being, even during times of crisis such as the COVID-19 pandemic. Trial RegistrationOSF Registries osf.io/f6djb; https://osf.io/vm3xq